Accident susceptibility index for a passenger ship-a framework and case study. (February 2022) - Montewka, Jakub; Manderbacka, Teemu; Ruponen, Pekka; Tompuri, Markus; Gil, Mateusz; Hirdaris, Spyros
Highlights: Framework linking relevant and observable factors to accident susceptibility (AS) at sea are established. Waterway, traffic and environment complexity determine navigator performance thus AS. Domain knowledge is elicited from experts, enhanced with vast aviation experience. Case studies covering 8 months of data reveal good correspondence of the framework with reality. Abstract: The continuous monitoring and assessment of operational vulnerability and accident susceptibility of passenger ships is crucial from the perspective of ship and passenger safety. Despite the existing solutions for vulnerability monitoring, stemming mainly from watertight door operations, a comprehensive framework for accident susceptibility assessment and monitoring is missing in the literature. Therefore, this paper offers a straightforward approach, utilizing heuristics rooted in the solid foundations of the first principles related to human performance. The proposed approach allows the evaluation of accident susceptibility of a ship in operation involved in open-sea and coastal navigation. The framework presented is based on observable and relevant factors, known to affect the navigator's performance, and as a consequence accident probability. The layout of the framework as well as the parameters of the developed model are based on literature survey in maritime and aviation domains, knowledge elicited from maritime experts and extensive simulations with the use of an in-house developed ship-ship encounter simulator. Subsequently, the model is applied to selected case studies, involving two distinctive ship types, namely a large cruise ship and a RoPax vessel. The results obtained for the case study presented in this paper reveal that most of their time the analyzed ships operate with negligible accident susceptibility (87%), while 1% of the cases are labelled as very high accident susceptibility. The remaining share of 12% is distributed among low, moderate and high values of accident susceptibility. The results are in line with earlier studies conducted in the same area but adopting different methods. The proposed solution can be applied as an onboard decision support tool, evaluating the operational accident susceptibility and vulnerability, thus increasing the crew's situational awareness. Additionally, it can be applied to historical data, allowing ship navigational safety diagnosis and implementation of appropriate countermeasures.